Survival and Prognostic Factors Comparing Stage IB 1 versus Stage IB 2 Cervical Cancer Treated with Primary Radical Hysterectomy - Srisomboon J. (2014)
This study was undertaken to compare the survival rates of stage IB 1 versus stage IB 2 cervical cancer patients and to evaluate the prognostic factors after treatment primarily with radical hysterectomy and pelvic lymphadenectomy (RHPL). Patients with stage IB cervical cancer undergoing primary RHPL at Chiang Mai University Hospital between January 2002 and December 2009 were evaluated for survival and recurrence. Clinicopathological variables were analyzed to identify the prognostic factors affecting the survival of the patients. During the study period, RHPL was performed on 570 stage IB 1 and 110 stage IB 2 cervical cancer patients. With a median follow-up of 48 months, the 5-year disease-free survivals were 98.1% and 82.8% respectively (p<0.001). Multivariate analysis identified four significant prognostic factors affecting survival including sub-staging, non-squamous cell carcinoma histology, lymph node metastasis and the presence of lymph-vascular space invasion. In conclusion, with a primary radical hysterectomy, stage IB 1 cervical cancer patients have a significantly better survival rate than those with stage IB 2. Significant prognostic factors for stage IB cervical cancer include tumor histology, nodal status, and the presence of lymph-vascular space invasion.